Review of sarcocystosis in Malaysia - Kan, S.P.; Pathmanathan, R. (1991)
Sarcocystis is a tissue coccidian with an obligatory two-host life cycle. The sexual generations of gametogony and sporogony occur in the lamina propria of the small intestine of definitive hosts which shed infective sporocysts in their stools and present with intestinal sarcocystosis. Asexual multiplication occurs in the skeletal and cardiac muscles of intermediate hosts which harbor Sarcocystis cysts in their muscles and present with muscular sarcocystosis. In Malaysia, Sarcocystis cysts have been reported from many domestic and wild animals, including domestic and field rats, moonrats, bandicoots, slow loris, buffalo, and monkey, and man. The known definitive hosts for some species of Sarcocystis are the domestic cat, dog and the reticulated python. Human muscular sarcocystosis in Malaysia is a zoonotic infection acquired by contamination of food or drink with sporocysts shed by definitive hosts. The cysts reported in human muscle resembled those seen in the moonrat, Echinosorex gymnurus, and the long-tailed monkey, Macaca fascicularis. While human intestinal sarcocystosis has not been reported in Malaysia so far, it can be assumed that such cases may not be infrequent in view of the occurrence of Sarcocystis cysts in meat animals, such as buffalo. The overall seroprevalence of 19.8% reported among the main racial groups in Malaysia indicates that sarcocystosis (both the intestinal and muscular forms) may be emerging as a significant food-borne zoonotic infection in the country.